Documentary sources on Navarre history from 1483 to 1512 in the Section of Clergy of the Historical National Archive - Muñoz-Cobo Sanz, Pilar (Huarte de San Juan. Geografía e Historia, 2021)
The author describes the documentary sources related to Catalina I and Juan III’s Kingdom between 1483-1512 years.